Potential and challenges for large-scale near-net-shaping of 7xxx aerospace grade aluminum via additive friction stir deposition - Hang Z. Yu; Greg D. Hahn (Materials Letters: X, 2023)
This letter examines the potential and challenges of using additive friction stir deposition for large-scale near-net-shaping of 7xxx Al alloys, particularly AA7075 and AA7050. Compared to fusion-based additive manufacturing, which is unable to print these alloys without feedstock modification or composition change, additive friction stir deposition is an emerging solid-state additive process with a thermomechanical processing nature that can render fully-dense AA7075 and AA7050 in the as-deposited state. More importantly, wrought-like tensile properties have been demonstrated in the deposited AA7075 based on the original composition. The process is well-suited for large-scale printing due to its high build rate and scalability. Significant challenges nevertheless exist in process and post-process control, in addition to the impurity from lubrication.